Viral Diseases of the Central Nervous System - Swanson, Phillip A. (Curr Opin Virol, 2015)
Virus-induced diseases of the central nervous system (CNS) represent a significant burden to human health worldwide. The complexity of these diseases is influenced by the sheer number of different neurotropic viruses, the diverse routes of CNS entry, viral tropism, and the immune system. Using a combination of human pathological data and experimental animal models, we have begun to uncover many of the mechanisms that viruses use to enter the CNS and cause disease. This review highlights a selection of neurotropic viruses that infect the CNS and explores the means by which they induce neurological diseases such as meningitis, encephalitis, and myelitis.